Cult of glory : the bold and brutal history of the Texas Rangers - Swanson, Doug J., 1953- (Viking, 2020)
"A twenty-first-century reckoning with the legendary Texas Rangers that does justice to their heroic moments while also documenting atrocities, brutality, and corruption The Texas Rangers rode into existence in 1823, when Texas was still part of Mexico, and continue today as one of the most famous of all law enforcement agencies. In Cult of Glory, Doug J. Swanson offers a sweeping account of the Rangers that chronicles both their epic, daring escapades and how the white and propertied power structures of Texas have used them as enforcers and protectors"--